Role of non-functionalized oxide nanoparticles on mechanical properties and toughening mechanisms of epoxy nanocomposites. Issue 16 (15th August 2021) - Goyat, M.S.; Hooda, Amrita; Gupta, Tejendra K.; Kumar, Kaushal; Halder, Sudipta; Ghosh, P.K.; Dehiya, Brijnandan S.
Abstract: Over the past few decades, the use of epoxy resins has gained significant attention from worldwide researchers due to its advantages in structural applications in various sectors like automotive, construction, and aerospace industries. This article summarizes and reviews the research on mechanical properties and toughening mechanism of epoxy composites filled with non-functionalized oxide nanoparticles. The incorporation of nanomaterials into the polymer matrix has been considered to be the most effective route to improve the mechanical properties of polymer composites. But the inherent brittle nature and cross-linking ability of epoxy makes it vulnerable to crack initiation and crack growth and limits its use in advanced structural applications. Recently, various kinds of nanofillers such as carbon nanotubes (CNTs), organic and inorganic oxide nanoparticles have attracted industrial interest due to their excellent mechanical, thermal, and electrical properties which can provide a dramatic improvement in the properties of epoxy composites but their dispersion issue, agglomeration and bundling problems deteriorate several important mechanical parameters of the epoxy composites. To date, no review article focused on the role of non-functionalized oxide nanoparticles on the improvement in mechanical properties of the reinforced epoxy composites. This review article assesses and summarizes some most recent findings on the de-agglomeration process, mechanical properties, and toughening mechanisms of epoxy nanocomposites reinforced with four types of most preferred non-functionalized oxide nanoparticles such as Al2 O3, TiO2, SiO2, and ZrO2 .